Synthesis and olfactory evaluation of spiro tricyclic diether structures. (15th November 2016) - Ondet, Pierrick; Plessis, Caroline; Lemière, Gilles; Duñach, Elisabet
Abstract: Readily available dienols were efficiently synthesised and cycloisomerised using a low catalyst loading of bismuth(III) triflate on the gram‐scale. Appealing complex tricyclic structures featuring a spirocyclic ether motif were obtained in very good yields. The olfactory properties of these original compounds has been assessed and pleasant fresh and woody notes from moderate to high intensity were noticed. In general, 2‐oxanorbornane compounds possess woody notes whereas analogous 7‐oxanorbornanes present greener tonalities. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Readily available dienols were efficiently synthesised and cycloisomerised using a low catalyst loading of bismuth (III) triflate on the gram‐scale. Appealing complex tricyclic structures featuring a spirocyclic ether motif were obtained in very good yields. The olfactory properties of these original compounds has been assessed and pleasant fresh and woody notes from moderate to high intensity were noticed. In general, 2‐oxanorbornane compounds possess woody notes whereas analogous 7‐oxanorbornanes present greener tonalities.